A case-based methodology for investigating urban comfort through interpretive research and microclimate analysis in post-earthquake Christchurch, New Zealand. (May 2019) - Tavares, Silvia G; Swaffield, Simon R; Stewart, Emma J
This paper explores how an interpretive case-based research strategy can reveal new empirical and theoretical insights into microclimate design. Innovative fieldwork in Christchurch, New Zealand investigated the nature and social meanings of urban comfort in a city with a seasonal climate featuring microclimatic variability, and with a physical landscape undergoing rapid change following a series of major earthquakes. Ethnographic methods were combined with microclimate measurements in four Christchurch-based case study locations to identify ways in which people adjust their cultural and lifestyle values and expectations to the actual microclimatic conditions. The field investigation had to capture data relevant to the microclimatic variability and be suitable for rapidly changing urban settings. Results suggest this integrative methodology successfully adapts to challenging physical contexts, and is able to provide a coherent body of evidence. Important insights revealed through this methodology may not have become apparent if only conventional microclimate methods were used.